If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 9x + 2 = 3x + -2 Reorder the terms: 2 + 9x = 3x + -2 Reorder the terms: 2 + 9x = -2 + 3x Solving 2 + 9x = -2 + 3x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-3x' to each side of the equation. 2 + 9x + -3x = -2 + 3x + -3x Combine like terms: 9x + -3x = 6x 2 + 6x = -2 + 3x + -3x Combine like terms: 3x + -3x = 0 2 + 6x = -2 + 0 2 + 6x = -2 Add '-2' to each side of the equation. 2 + -2 + 6x = -2 + -2 Combine like terms: 2 + -2 = 0 0 + 6x = -2 + -2 6x = -2 + -2 Combine like terms: -2 + -2 = -4 6x = -4 Divide each side by '6'. x = -0.6666666667 Simplifying x = -0.6666666667
| 9x^2-6x-4=4 | | b+5-96=-48 | | 14x+8=17x-19 | | .40x=-4 | | 33j=198 | | 3x^2+5=32 | | 33j=197 | | b+8-96=-48 | | 216=n/2 | | 36=36p | | 4a-7=0 | | 45m=90 | | (-4)-s=0 | | (-9)=s+(-4) | | 60-g=6 | | (-10)=n-8 | | 36-x=7(7x+11)+9 | | (-2)-k=4 | | (-14)=r-6 | | 12n=-5 | | 9=j+7 | | -8+7x=7x-8 | | v+(-3)=(-10) | | 2(4-2(3-x))-1=4(2(4x-3)+7)-25 | | 3x^2-24+48 | | g(x)=-2[[x]] | | 8=r+4 | | 85x=24 | | (-16)=(-9)-w | | 5-.75s=-1 | | (4x+1)^2=7 | | y=-2[[x]] |